2019
DOI: 10.1016/j.ajo.2019.01.026
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Prevalence and Incidence of Dry Eye Disease Based on Coding Analysis of a Large, All-age United States Health Care System

Abstract: To assess overall prevalence, annual prevalence, and incidence of dry eye disease (DED) in a large, representative population in the United States.DESIGN: Prevalence and incidence study. METHODS: Retrospective analysis using the Department of Defense (DOD) Military Health System (MHS) data on beneficiary medical claims from United States DOD military and civilian facilities, January 1, 2003 through March 31, 2015. PATIENT POPULATION: Using an algorithm, medical diagnostic codes indicative of DED and prescripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
150
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 167 publications
(168 citation statements)
references
References 21 publications
8
150
0
10
Order By: Relevance
“…Notably, there are several authors who have determined 2 broad categories of symptoms in the diagnosis of CVS [49,57]: a first group of internal symptoms (including blurred vision, diplopia or headache) generally caused by refractive, accommodative or vergence anomalies and a second group of external symptoms related to dry eye (including burning, itching, dryness or tearing). Female sex is one of the most consistent risk factors in the development of dry eye, becoming more significant with age [58,59]. Two studies conducted with North American populations of more than 39,000 women [55] and 25,000 men [56] showed that women had a 70% higher risk of dry eye than did men.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, there are several authors who have determined 2 broad categories of symptoms in the diagnosis of CVS [49,57]: a first group of internal symptoms (including blurred vision, diplopia or headache) generally caused by refractive, accommodative or vergence anomalies and a second group of external symptoms related to dry eye (including burning, itching, dryness or tearing). Female sex is one of the most consistent risk factors in the development of dry eye, becoming more significant with age [58,59]. Two studies conducted with North American populations of more than 39,000 women [55] and 25,000 men [56] showed that women had a 70% higher risk of dry eye than did men.…”
Section: Discussionmentioning
confidence: 99%
“…5 Similarly, in a large U.S. database, the overall prevalence of DED between 2003 and 2015, based on diagnostic codes and pharmacy claims, was 5.3%. 6 Both analyses found that the prevalence of DED was higher among women than men and increased with age. 5,6 Another large U.S. claims database analysis showed that DED represented the sixth most common ocular condition for which patients sought care.…”
Section: Introductionmentioning
confidence: 97%
“…But the direct interaction between blood vessels and nerves in the cornea, especially during inflammation, has not been studied . Dry eye disease (DED) is the most common ocular surface inflammatory disease with an overall prevalence of 5.28% in the US population . Both human and animal studies have shown structural and functional alterations of corneal nerves in DED .…”
Section: Introductionmentioning
confidence: 99%